Efeito de Hidroxietilamido sobre Lesão Renal Aguda em Modelo de Isquemia-Reperfusão Hepática - Oliveira-Santos, M (2012)
BACKGROUND: Hepatic vascular control techniques employed during liver surgery are usually associated with ischemia-reperfusion injury, which could cause acute renal dysfunction. The murine model has been used in the study of this injury. Hydroxyethyl starch has recognized anti-inflammatory properties and improves microcirculation. Third generation hydroxyethyl starches, namely 130/0.4, show a better safety profile than previous molecules. OBJECTIVES: Evaluation of renal injury in a murine model of partial normothermic hepatic ischemia-reperfusion injury and assessment of hydroxyethyl starch 130/0.4 effect on this injury. METHODS: Seventy-two male Wistar rats were randomized into six groups with identical characteristics (n = 12 x 6). In three of them, the ischemia-reperfusion injury groups, we placed a clamp in the vascular pedicle of the median and left liver lobes, inducing hepatic ischemia (70%), and removed the clamp 60 minutes later (IRI + HES and IRI + HS groups, with HES or hypertonic saline (7.5%) administration during reperfusion, respectively, and IRI group, without fluid therapy). The control groups were sham-operated without hepatic ischemia and treated likewise (sham + HES, sham + HS and sham groups). After 120 minutes of reperfusion in the ischemia-reperfusion injury groups and 180 minutes in the controls we drew blood from the aorta artery for creatinine, urea and alanine aminotransferase quantification and removed kidney and liver samples for histopathological analysis. RESULTS: As already published by our group, the partial hepatic ischemia-reperfusion injury model showed liver injury. In the present work, the IRI group had higher creatinine, urea and histopathological score than sham (p < 0.05). Creatinine and urea mean concentrations were significantly lower both in IRI+HES (23.08 µmol/L and 8.38 mmol/L, respectively) and IRI + HS (26.59 µmol/L and 7.82 mmol/L) when compared to IRI (40.101 µmol/L and 11.25 mmol/L). There was no significant difference between IRI + HES and IRI + HS groups (serum markers and histopathology).Conclusion: The hepatic ischemia-reperfusion injury murine model was effective in producing kidney injury. Both the hydroxyethyl starch 130/0.4 and the hypertonic saline protected the kidney in this context and were not harmful for this organ in the controls. Further studies are necessary to assess clinical implications of hydroxyethyl starch 130/0.4 administration in liver surgery.